2017
DOI: 10.4317/medoral.21512
|View full text |Cite
|
Sign up to set email alerts
|

‘Reliability of new poly (lactic-co-glycolic acid) membranes treated with oxygen plasma plus silicon dioxide layers for pre-prosthetic guided bone regeneration processes’

Abstract: BackgroundThe use of cold plasmas may improve the surface roughness of poly(lactic-co-glycolic) acid (PLGA) membranes, which may stimulate the adhesion of osteogenic mediators and cells, thus accelerating the biodegradation of the barriers. Moreover, the incorporation of metallic-oxide particles to the surface of these membranes may enhance their osteoinductive capacity. Therefore, the aim of this paper was to evaluate the reliability of a new PLGA membrane after being treated with oxygen plasma (PO2) plus sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Figure 4 shows the macroscopic appearance of the PLGA membranes before and after surface treatment with oxygen plasma. Additional information about the PLGA membranes after and before the oxygen plasma treatments can be found elsewhere [1,2,[30][31][32][33]. Surface topography analysis also enables us to appreciate the considerable increase in surface roughness of the PLGA membrane after exposure to oxygen plasma, with an RMS roughness value greater than 300 nm, without affecting structural integrity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the macroscopic appearance of the PLGA membranes before and after surface treatment with oxygen plasma. Additional information about the PLGA membranes after and before the oxygen plasma treatments can be found elsewhere [1,2,[30][31][32][33]. Surface topography analysis also enables us to appreciate the considerable increase in surface roughness of the PLGA membrane after exposure to oxygen plasma, with an RMS roughness value greater than 300 nm, without affecting structural integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the macroscopic appearance of the PLGA membranes before and after surface treatment with oxygen plasma. Additional information about the PLGA membranes after and before the oxygen plasma treatments can be found elsewhere [ 1 , 2 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Membranes that were conditioned with PO 2 and then incorporated with SiO 2 provided significantly higher bone regeneration and mineralised bone length. This kind of membrane also showed a better influence on osteoclast concentration and improved osteosynthetic activity [26]. It can be concluded that both SiO 2 and TiO 2 incorporation significantly influenced bone regeneration, and this can be a valuable direction of future clinical research on GBR membrane modification.…”
Section: Discussionmentioning
confidence: 99%